Mechanisms of high temperature corrosion : a kinetic approach - Sarrazin, Pierre (Trans Tech Publications Ltd., 2008)
The oxidation of metals is, by definition, a reaction between a gas and a solid which usually produces a solid reaction product. At first glance, this would therefore seem to be a very simple process but, in fact, it is considerably more complex. One would like to think that the reaction product, i.e., the scale that forms on the metal, acts as a physical barrier between the reactants, and that the reaction should thus cease once the barrier is established. We know that this is unfortunately not the case, because transport of matter through the scale allows the reaction to continue. We also kn.
Keywords: Corrosion and anti-corrosives.; Materials at high temperatures -- Corrosion.; elektronické knihy; electronic books